TEORI KARIR SOSIAL KOGNITIF DALAM PRAKTIK BIMBINGAN KONSELING - Harahap, Annisa Ihsani; Fadhli, Teuku; Adelia , Rizky Rindi; Lubis, Siti Rahayu; Asyham, Dymas Adietya; Abdillah, Rajus Sya’abi (Yayasan Insan Cipta Medan, 2024)
Social Cognitive Career Theory (SCCT) is an important theoretical approach to understanding the influence of social and cognitive factors on a person's career development. Social cognitive career theory (SCCT) aims to explain three relevant aspects, namely self-efficacy beliefs, outcome expectations, and personal goals. Social cognitive theory provides counselors with an understanding of how to increase self-efficacy beliefs and their effectiveness for both clients and themselves. Three aspects of career development are interrelated: how academic and career principles are formed, how educational and career choices are made, and how academic and career success is achieved. This research used a qualitative descriptive approach and the type of research was library research. Literary research is carried out by reading, taking notes and processing then making one sentence from various book sources that have been read. In this context, this article explores the key concepts of SCCT and their relevance in the context of career development. The aim of this research is to determine the impact of cognitive and social factors that influence career decision making and its implementation in educational career counseling, with the hope of contributing to the understanding of individual career dynamics.